1997
DOI: 10.1002/(sici)1097-0096(199710)25:8<431::aid-jcu4>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal sonographic assessment of premalignant and malignant changes in the endometrium in postmenopausal bleeding

Abstract: Purpose We explored the value of transvaginal sonography as a screening technique for endometrial abnormalities. Methods Transvaginal sonography was used to evaluate the likelihood that an endometrial abnormality was present in a group of 103 women with postmenopausal bleeding. Results Sonographic findings showed a mean endometrial thickness of 6.2 mm in patients with endometrial atrophy, 12.4 mm in patients with simple hyperplasia, 13.4 mm in patients with complex hyperplasia, and 14.1 mm in patients with end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
11

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 20 publications
1
12
0
11
Order By: Relevance
“…It was absent or difficult to assess in the 3 cases (1.5%) that were diagnosed as endometrial cancer. Fistonic et al 18 assessed the various features of malignancy and found 100% sensitivity for an irregular myometrial‐endometrial interface in predicting endometrial carcinoma. Using the interface as one of the criteria, none of the cases with a benign diagnosis were misdiagnosed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It was absent or difficult to assess in the 3 cases (1.5%) that were diagnosed as endometrial cancer. Fistonic et al 18 assessed the various features of malignancy and found 100% sensitivity for an irregular myometrial‐endometrial interface in predicting endometrial carcinoma. Using the interface as one of the criteria, none of the cases with a benign diagnosis were misdiagnosed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Am häufigsten wurden die cut-off-Level 4 mm und 5 mm untersucht, wobei unterhalb dieser Werte (£ 4 mm bzw. £ 5 mm) mit großer Sicherheit ein Endometriumkarzinom auszuschließen ist, aber darüber eine große Zahl falsch positiver Befunde zu finden ist [6, 30,40,56,70,79]. Neben den angeführten Arbeiten existieren 3 Metaanalysen, die dieses Resultat bestäti-gen [12,42,78]: Gupta et al (57 Studien,9 031 Patientinnen) folgerten, dass bei einem negativen Ergebnis, unter Anwendung eines cut-off-Level von £ 5 mm, eine endometriale Pathologie (Endometriumhyperplasie oder ein Karzinom) mit großer Sicherheit ausgeschlossen werden kann, da hiermit die Wahrscheinlichkeit einer endometrialen Erkrankung von 26 auf 2,7 % und eines Karzinoms von 14 auf 2,5 % vermindert wurde [42].…”
Section: Introductionunclassified
“…Die Ergebnisse zeigen, dass die Messung der Endometriumdicke bei PMB eine hohe Sensitivität für die Erkennung des Endometriumkarzinoms aufweist, aber eine geringe Spezifität [12,30,49]. Neben dem Karzinom können sich Polypen und Hyperplasien hinter einem verbreiterten Endometrium verbergen [12].…”
Section: Introductionunclassified
“…In 1995, Weigel and colleagues 29 suggested that adding assessment of the endometrium for homogeneity, presence of a central echo, and echogenicity would be most useful in diagnosing cancers in women whose endometrial thickness is in the ''gray area'' of 4-10 mm. Another prospective trial 30 found a 100% sensitivity for irregular myometrial-endometrial interface in predicting endometrial carcinoma. When intrauterine fluid is present, the measurement of endometrial thickness includes only 2 fine walls of the endometrium and excludes the fluid.…”
Section: Endometrial-myometrial Interfacementioning
confidence: 99%